Genotoxic and antigenotoxic medicinal plant extracts and their main phytochemicals: “A review” - Al-Naqeb, Ghanya; Kalmpourtzidou, Aliki; Giampieri, Francesca; De Giuseppe, Rachele; Cena, Hellas (Frontiers in Pharmacology, 2024)
Many medicinal plant extracts have been proven to have significant health benefits. In contrast, research has shown that some medicinal plant extracts can be toxic, genotoxic, mutagenic, or carcinogenic. Therefore, evaluation of the genotoxicity effects of plant extracts that are used as traditional medicine is essential to ensure they are safe for use and in the search for new medication. This review summarizes 52 published studies on the genotoxicity of 28 plant extracts used in traditional medicine. A brief overview of the selected plant extracts, including, for example, their medicinal uses, pharmacological effects, and primary identified compounds, as well as plant parts used, the extraction method, genotoxic assay, and phytochemicals responsible for genotoxicity effect were provided. The genotoxicity effect of selected plant extracts in most of the reviewed articles was based on the experimental conditions. Among different reviewed studies, A total of 6 plant extracts showed no genotoxic effect, other 14 plant extracts showed either genotoxic or mutagenic effect and 14 plant extracts showed anti-genotoxic effect against different genotoxic induced agents. In addition, 4 plant extracts showed both genotoxic and non-genotoxic effects and 6 plant extracts showed both genotoxic and antigenotoxic effects. While some suggestions on the responsible compounds of the genotoxicity effects were proposed, the proposed responsible phytochemicals were not individually tested for the genotoxicity potential to confirm the findings. In addition, the mechanisms by which most plant extracts exert their genotoxicity effect remain unidentified. Therefore, more research on the genotoxicity of medicinal plant extracts and their genotoxicity mechanisms is required.